Implementation of surveillance plans for cyanobacteria in bathing waters: a case study from Lake Garda - Chiara Zampieri; Federica Giacomazzi; Giorgio Franzini (Advances in Oceanography and Limnology)
Since the beginning of the 1990s, Lake Garda has been affected by the development of surface blooms caused by the cyanobacterium Dolichospermum lemmermannii. Moreover, several other potentially toxigenic cyanobacteria were identified in the water samples collected during the monitoring activities, including the microcystins producer Planktothrix rubescens and a new species able to synthesize anatoxins (Tychonema bourrellyi). A plan has been activated by ARPAV (Regional Agency for Environmental Prevention of Veneto) to monitor algal communities and assess any risk of cyanobacterial proliferation that could affect the lake ecosystem and the bathing areas. In this work, we will briefly describe and critically comment on the main results obtained from the monitoring activities.